Status of Land Degradation in India - Sethi, R.M.; Nair, G.K.; Seshagiri, K.V.; Singh, R.R. (Journal of Soil and Water Conservation, 2022)
Accurate data on land degradation has become largely elusive with varied statistics projected by different organisations during the last two decades. The reported figures have been found to be mere assessments based on secondary information. Data generated by organisations like National Remote Sensing Agency of Department of Space and National Bureau of Soil Survey & Land Use Planning were found to fall short of giving a true total picture because of scale limitations, as the bases used are on 1:1 million scale. Over and above this, the intensity of field verification was so weak that the reliability of the data generated could not be deemed satisfactory. The soil & Water Conservation Division of the Ministry of Agriculture is in need of realistic estimates of various types of land degradation for pragmatic planning since substantial funds are spent for programmes for amelioration of land. Pending launching of a detailed systematic survey programme, as a via media, a Central team was, constituted with the mandate: (i) Discussing the matter with all concerned departments of various States, and with direct data generating agencies (ii) Taking stock of available data and report and (iii) Achieving realistic estimates of land degradation; typezvise and Statewise on the basis of existing primary and secondary data. The results of the efforts of the team who have completed the studies in 20 States, are presented in this paper. The lacunae and discrepancies identified in the existing data, the methodology adopted by the Central team in assessing the Status of Land. Degradation, are discussed in detail. In a nutshell it has been found that out of the total geographical area of 283.15 mitt encompassing 20 States, an area of 98.53 ni.ha. constituting 34.7% is found to be affected by one or other major type of degradation. This is against the previously reported assessment of159.46 ni.ha. comprising 56.3% of geographical area. These results constitute preliminary estimates subject to approval by Government of India.